Kernel Smut of Rice: An Overview - R.C. SHARMA; INDU SHARMA; ROHIT AGGARWAL; ASHOK GAUR (Seed Research, 2026)
Kernel smut (Tilletia barclayana) of rice also referred as paddy bunt (Neovossia horrida) is worldwide in distribution. In India, large number of seed samples get rejected as the tolerance levels for the disease are prescribed at 0.1 and 0.5 per cent for foundation and certified seed, respectively. In USA, the disease has been occurring persistently for the last 50 years in Arkansas and adjoining rice growing areas causing significant quantitative as well as qualitative losses. There is voluminous literature available on the distribution, economic importance, etiology, epidemiology, disease cycle and management of this disease which is reviewed in this article.